THE WEST FRONT OF TINTERN ABBEY CHURCH, MONMOUTHSHIRE. (23rd July 2015) - Morris, †Richard K; Coldstream, Nicola; Turner, Rick
Abstract : The conservation and repair of the west front of Tintern Abbey church, undertaken by Cadw between 2005 and 2010, provided an unrivalled opportunity to survey, record and analyse the design, construction and alteration of a much-celebrated example of medieval architecture. This paper considers in detail the moulding profiles and ornament of the west front and offers a developmental history for this part of the abbey church. Comparisons are made with ecclesiastical architecture elsewhere in England and Wales, and with the contemporary programme of work being undertaken at nearby Chepstow Castle. Two appendices outline the history of its conservation since 1900 and assess some Victorian drawn records of the west front. RÉSUMÉ: Les travaux de conservation et de réparation effectués sur la façade occidentale de l'église de Tintern Abbey par Cadw entre 2005 et 2010, ont offert une occasion inégalée d'étudier, de consigner et d'analyser la conception, la construction et les modifications de ce très célèbre exemple de l'architecture médiévale. Le présent article examine dans les détails les moulures et décorations de la façade ouest et présente un compte rendu du développement de cette partie de l'abbatiale. Des comparaisons sont établies avec des édifices médiévaux d'autres endroits de l'Angleterre et du Pays de Galles et avec le programme de travaux entrepris à la même époque au château de Chepstow voisin. L'histoire de sa conservation depuis 1900 est décrite dans deux annexes qui examinent également les dessins de la façade ouest effectués à l'époque victorienne. ZUSAMMENFASSUNG: Die Konservierungs- und Reparaturarbeiten an der Westfassade der Kirche von Tintern Abbey, die von Cadw zwischen 2005 und 2010 durchgeführt wurden, lieferten die einzigartige Möglichkeit, Entwurf, Konstruktion und Änderungen an diesem vielgerühmten Beispiel mittelalterlicher Architektur zu studieren, aufzunehmen und zu analysieren. Diese Abhandlung untersucht auf eingehende Weise die Formprofile und Ornamente der Westfassade und bringt eine Entwicklungsgeschichte zu diesem Teil der Abteikirche. Vergleiche werden mit sakralen Bauwerken in anderen Teilen von England und Wales und mit dem derzeit am Chepstow Castle durchgeführten Arbeitsprogramm gezogen. Zwei Anhänge umreißen die Geschichte der Konservierung seit 1900 und bewerten einige viktorianische Aufzeichnungen zur Westfassade.